Analisis Rasio Profitabilitas Terhadap Kinerja Keuangan BCA Syariah (Studi Kasus Laporan Tahun 2019-2023) - Ramadhan, Azhar Zahira (Maliki Interdisciplinary Journal, 2025)
This study analyzes the financial performance of BCA Syariah using profitability ratios from 2019 to 2023, including Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operational Cost to Operational Income (BOPO). The results indicate an average ROA of 1.24%, below Bank Indonesia's optimal standard (>1.5%), although it reached the standard in 2023. The average ROE was 3.92%, significantly lower than BI's standard of 15%. The average NIM stood at 4.72%, close to BI’s 5% benchmark and exceeded it in 2022. Meanwhile, the average BOPO of 83.78% exceeded the ideal efficiency range of 50%-75%, despite annual improvements. This study recommends enhancing operational efficiency through better cost management and digital technology utilization, alongside investment diversification to optimize equity. These steps are expected to improve profitability and strengthen BCA Syariah's competitiveness in the Islamic banking market.